2017
DOI: 10.1177/0971685816673487
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of Learning Agility and Authentic Leadership Development: Moderating Effects of Learning Goal Orientation and Organizational Culture

Abstract: The present article attempts to examine the relationship between learning agility and authentic leadership development. The recent rise in the cases of fraud involving leaders at various levels in the organizations, and the resulting distrust among the employees towards their leaders, points to the need to have authentic leaders, given the positive organizational outcomes associated with this leadership approach. Further, scholars have suggested that leadership development is possible through learning from one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
(57 reference statements)
1
15
0
1
Order By: Relevance
“…Organizational culture was considered the second most important factor in successful executive succession planning, which was also supported by previous studies (Gothard & Austin, 2013; Mehrtak et al, 2017; Mugo et al, 2015). The third factor was leadership development opportunities, consistent with studies that found that leadership development, as a component of executive succession planning, leads to employee satisfaction and enhances organizational performance (Manning et al, 2015; Stewart & Kuenzi, 2018; Yadav & Dixit, 2017).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Organizational culture was considered the second most important factor in successful executive succession planning, which was also supported by previous studies (Gothard & Austin, 2013; Mehrtak et al, 2017; Mugo et al, 2015). The third factor was leadership development opportunities, consistent with studies that found that leadership development, as a component of executive succession planning, leads to employee satisfaction and enhances organizational performance (Manning et al, 2015; Stewart & Kuenzi, 2018; Yadav & Dixit, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…However, this does not minimize its impact on effective executive succession planning, because many previous studies have found that it influences the process by allowing new executives the space to lead in their own way. A smooth leadership transition requires the support of all levels in the organization, but especially from the organization’s leaders, including the board (Ciampa, 2016; Gothard & Austin, 2013; Yadav & Dixit, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership agility is an increasingly recognized construct in talent management as a key factor for long-term leadership effectiveness (Yadav & Dixit, 2017). Learning agility is the best predictor of an individual's future performance.…”
Section: Introductionmentioning
confidence: 99%
“…Навчальна гнучкість (Learning Agility) -це готовність та здатність навчатися на власному досвіді, з подальшим застосуванням цих знань для успішного виконання своїх обов'язків у нових та незнайомих ситуаціях [2]. Дане поняття включає в себе не лише швидкість навчання, а й легкість руху між різними ідеями, точками зору та ситуаціями, що дозволяє формувати нові, нетрадиційні та більш ефективні шляхи для вирішення проблем та побудови процесів.…”
unclassified